2006
DOI: 10.1158/0008-5472.can-05-1265
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Human Tumor Antigen Interleukin-13 Receptor α2 Chain

Abstract: The interleukin (IL)-13 receptor A2 (IL-13RA2) chain is a primary binding and internalization subunit for a Th2-derived immune regulatory cytokine, IL-13. Although extremely high levels of IL-13RA2 chain are expressed on a variety of human tumor cells and specimens, its precise role in tumor immunology has not been defined. To investigate the role of IL-13RA2 in tumor immunity, we used D5 melanoma cells stably transfected with the human IL-13RA2 gene (D5A2) to assess the effect of an IL-13RA2 DNA vaccine in im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…Since this chain is overexpresed in a variety of human primary as well as metastatic tumors, we predict that IL-13Ra2 targeted agents such as IL-13PE (composed of IL-13 and truncated Pseudomonas exotoxin) will not only target primary tumors but also metastatic lesions. 6,18,32,34 As we have previously shown that IL-13Ra2 is a tumor rejection antigen 35 and a target for receptor directed cancer vaccines, a combination therapy with targeted immunotoxin will be a useful strategy to target primary and metastatic tumors. These studies are currently ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Since this chain is overexpresed in a variety of human primary as well as metastatic tumors, we predict that IL-13Ra2 targeted agents such as IL-13PE (composed of IL-13 and truncated Pseudomonas exotoxin) will not only target primary tumors but also metastatic lesions. 6,18,32,34 As we have previously shown that IL-13Ra2 is a tumor rejection antigen 35 and a target for receptor directed cancer vaccines, a combination therapy with targeted immunotoxin will be a useful strategy to target primary and metastatic tumors. These studies are currently ongoing in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 is known to regulate airway hyperresponsiveness and allergic inflammation by binding to heterodimers of IL-13R␣1 and IL-4R␣ (9 -16). Another IL-13 receptor, IL-13R␣2, binds IL-13 with high affinity and, in contrast to IL-13R␣1, is a decoy receptor and a negative regulator of IL-13-induced biological functions (17)(18)(19)(20)(21)(22)(23)(24)(27)(28)(29). In HBEpCs, we found that LPA treatment increased IL-13R␣2 gene expression and protein production without affecting IL-13R␣1 and IL-4R␣ (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its function in a Th2-dominant immune response, IL-13R␣2 is being investigated as a therapeutic target for many human cancers, including prostate tumor, pediatric brain tumor, and breast and pancreatic tumors (22)(23)(24). Although plasma LPA levels are elevated in ovarian and breast cancer (58), no causal relationship has been proposed between LPA and IL-13R␣2 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Infected cells were selected with puromycin (1 μg/mL) for 7 days. IL-13Rα2 overexpression in HPAF-II was determined as described previously (27).…”
Section: Methodsmentioning
confidence: 99%